2016
DOI: 10.1016/j.jsams.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and performance effects of carbohydrate gels consumed prior to the extra-time period of prolonged simulated soccer match-play

Abstract: 18Objectives: The physiological and performance effects of carbohydrate-electrolyte gels consumed 19 before the 30 min extra-time period of prolonged soccer-specific exercise were investigated. 20Design: Randomised, double-blind, crossover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 28 publications
4
34
0
2
Order By: Relevance
“…However, in the absence of cerebral glucose measurement, these proposed mechanisms should be interpreted with caution. Nevertheless, this study supports findings of impaired physical, technical and cognitive performance in the latter stages of soccer-specific exercise and the enhancement of selected physical and technical performance markers following carbohydrate supplementation 1,6,20 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, in the absence of cerebral glucose measurement, these proposed mechanisms should be interpreted with caution. Nevertheless, this study supports findings of impaired physical, technical and cognitive performance in the latter stages of soccer-specific exercise and the enhancement of selected physical and technical performance markers following carbohydrate supplementation 1,6,20 .…”
Section: Discussionsupporting
confidence: 86%
“…Improved sprinting (speed: +2.7% vs. Wat), soccer dribbling (speed: >+3% vs. Wat and PL) and selfpaced exercise (mean number of self-paced accelerations >1.5 m•s -2 : >+25% vs. Wat and PL) performance occurred throughout CHO; reflecting previous observations when carbohydrate was consumed in beverages 6 , gels 20 , or mouth rinses 12 . Despite improved high-intensity performance in CHO, no between-trial effects were observed for RPE.…”
Section: Discussionsupporting
confidence: 80%
“…A similar, temporary decline in plasma glucose level and even hypoglycaemia has been observed in football players during the first half-time in studies by other authors (Russell et al 2011;Russell et al 2010;Kingsley et al 2014). This suggests that liver glycogen is sufficient to maintain plasma glucose level during a football game and even during the overtime period (Harper et al 2016). This is also one of the reasons why consumption of carbohydrate-rich drinks is not advised for team sport athletes during game/exercise, to maintain endogenous regulation of glycogen homeostasis and produce high performance of athletes even during the final stages of a prolonged exercise.…”
Section: Discussionsupporting
confidence: 63%
“…[52][53][54] Carbohydrate gels consumed before or during physical activity have been shown to improve some aspects of performance. 55,56 Like sport drinks, post-exercise consumption (within about 1 hour) of bars or gels will lead to greater repletion of muscle glycogen because post-exercise glucose transport and the activity of glycogen synthase (the ratelimiting enzyme for glycogen resynthesis) are considerably augmented. 57,58 Adverse Events…”
Section: Researchmentioning
confidence: 99%